Healthy teens, healthy schools : how media literacy education can renew education in the United States - Domine, Vanessa Elaine (Rowman and Littlefield, 2015)
"Widespread obesity, poor nutrition, sleep deprivation, and highly digital and sedentary lifestyles are just a few of the many challenges facing young people. Although public schools in the United States have the potential for meeting these challenges on a mass scale, they are slow to respond. ... This book illustrates holistic health education through school-community initiatives and innovative partnerships that are successful in magnifying all curriculum subjects and their associated teaching practices."--Back cover